PERLINDUNGAN HUKUM TERHADAP HAK-HAK ISTRI KORBAN KDRT PASCA PERCERAIAN BERBASIS NILAI KEADILAN DALAM HUKUM ISLAM DAN HUKUM NASIONAL - Patawari, Andi Yusri; kurniati, Kurniati; Misbahuddin, Misbahuddin (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
This article examines the issue of forms of legal protection for the rights of wives of domestic violence victims based on the values of justice. This is because victims of domestic violence are increasing from year to year, even though there is a Law on the Elimination of Domestic Violence, this phenomenon still continues. Therefore, this issue is important to study in order to get a clear picture of the forms of legal protection that can be obtained by victims of domestic violence. The research approach is a qualitative approach with a normative juridical scientific approach, the data is in the form of secondary data sourced from statutory regulations and studies of Islamic jurisprudence literature. In the discussion it was revealed that: Firstly, the forms of legal protection in legislation are classified into: 1). Preventive action, namely a form of legal protection by clearly regulating the rights and obligations of husband and wife, this has been regulated in the Marriage Law and KHI. 1). Repressive action, namely a form of legal protection when domestic violence has occurred, then this falls into the category of criminal law where the perpetrator is threatened with a crime, this has been regulated in the 2004 Domestic Violence Law. Secondly, in Islam legal protection is more comprehensive, by regulating the laws between husband and wife, both laws relating to civil matters during and after divorce. Likewise, Islam clearly provides legal protection for victims of domestic violence, by enforcing hudud penalties for perpetrators of domestic violence.